2021
DOI: 10.1021/jacs.1c10034
|View full text |Cite
|
Sign up to set email alerts
|

Photomodulation of Transmembrane Transport and Potential by Stiff-Stilbene Based Bis(thio)ureas

Abstract: Membrane transport proteins fulfill important regulatory functions in biology with a common trait being their ability to respond to stimuli in the environment. Various small-molecule receptors, capable of mediating transmembrane transport, have been successfully developed. However, to confer stimuli-responsiveness on them poses a fundamental challenge. Here we demonstrate photocontrol of transmembrane transport and electric potential using bis(thio)ureas derived from stiff-stilbene. UV–vis and 1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(47 citation statements)
references
References 58 publications
2
40
0
Order By: Relevance
“…The development of synthetic ion transporters such as self-assembled ion channels and mobile ion carriers has attracted significant interest, both as fundamental tools for investigating transmembrane ion transport and as potential therapeutics for diseases that arise from protein ion channel mis-regulation. Stimuli-responsive synthetic transporters, as artificial analogues of their protein counterparts, have potential utility in spatio-temporally targeted applications but remain comparatively rare . Synthetic channels and mobile ion carriers, which can be switched between inactive and active states, are highly desirable for achieving reversible, stimuli-responsive control over ion transport, but are particularly challenging to develop.…”
Section: Introductionmentioning
confidence: 99%
“…The development of synthetic ion transporters such as self-assembled ion channels and mobile ion carriers has attracted significant interest, both as fundamental tools for investigating transmembrane ion transport and as potential therapeutics for diseases that arise from protein ion channel mis-regulation. Stimuli-responsive synthetic transporters, as artificial analogues of their protein counterparts, have potential utility in spatio-temporally targeted applications but remain comparatively rare . Synthetic channels and mobile ion carriers, which can be switched between inactive and active states, are highly desirable for achieving reversible, stimuli-responsive control over ion transport, but are particularly challenging to develop.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a number of different approaches to controlling the activity of mobile ion carriers have been reported. 7 Photoswitchable transporters, based on a molecular photo-switch such as an azobenzene [17][18][19][20] or stilbene 21 with appended binding sites, allow for reversible activation by modulating the anion binding affinity. However, in these photo-switchable systems the OFF isomers typically have some background transport activity because they can inevitably bind anions to some extent.…”
Section: Introductionmentioning
confidence: 99%
“…6 Displacement ellipsoid plot (50% probability level) of cis-18eCCl À (CCDC 2111230). 71 magnitude larger than that in binding affinity, highlighting that the latter is not the determinant factor for the former. Additional mechanistic studies using cation co-transporters in various liposomal transport assays revealed that phenyl(thio) ureas 18a-b are highly selective for transporting Cl À (over H + and OH À ), i.e., they are electrogenic uniporters.…”
Section: Transport and Diffusionmentioning
confidence: 85%
“…In collaboration with the group of Gale, we studied the transmembrane transport properties of 18a–b as well as of p -trifluoromethyl- and p -nitro-substituted derivatives 18c–f (see Scheme 7A ). 71 Overall, 365 nm irradiation gave the highest conversion towards the cis isomers in case of the bis-thiourea compounds (47–52% vs. 35–51% for bis-thiourea and bis-urea, respectively), but at 385 nm irradiation the largest amount of trans isomer was recovered for the bis-ureas (93% for 18a, c vs. 74–83% for 18b, d). Furthermore, the PSS 365 ratio of the p -nitro-substituted variants was not altered by subsequent irradiation with 385 nm light as the absorption spectra of cis and trans isomers (while being red-shifted) were highly similar.…”
Section: Stiff-stilbenementioning
confidence: 88%